Composite material for enhancing toughness of polyformaldehyde material and preparation method thereof

By introducing components such as modified polyethylene, modified polytetrafluoroethylene and toughening agent, the composition and structure of polyformaldehyde materials are optimized, and problems such as insufficient strength and stiffness, limited heat resistance, and insufficient wear resistance in heavy-duty mechanical components are solved, which significantly improves its toughness and performance.

CN119613914APending Publication Date: 2025-03-14FUJIAN HUASU NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411700829.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

When used as heavy-load mechanical components, polyformaldehyde faces problems such as insufficient strength and stiffness, limited heat resistance, insufficient wear resistance, poor chemical resistance and poor long-term performance stability.

Method used

By introducing components such as modified polyethylene, modified polytetrafluoroethylene, toughener and modified filler, the composition and structure of polyformaldehyde materials are optimized and their toughness and performance are improved. Specific methods include modifying polytetrafluoroethylene, grafting carbon nanotubes to enhance their strength and wear resistance, and improving the notch impact strength and tensile strength of the material by modifying polyethylene by urea formaldehyde resin.

Benefits of technology

It significantly improves the toughness, wear resistance and notch impact strength of polyformaldehyde materials, maintains its original excellent mechanical strength and wear resistance, and improves the thermal deformation temperature and long-term performance stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005153261600000111
    Figure BDA0005153261600000111
  • Figure BDA0005153261600000121
    Figure BDA0005153261600000121
Patent Text Reader

Abstract

The invention belongs to the technical field of polyformaldehyde materials, and particularly relates to a composite material for enhancing the toughness of a polyformaldehyde material and a preparation method of the composite material. Comprising the following components in parts by weight: 100 parts of polyformaldehyde, 10-20 parts of modified polyethylene, 5-15 parts of modified polytetrafluoroethylene, 5-10 parts of a flexibilizer, 8-15 parts of a modified filler, 0.8-1.2 parts of an antioxidant, 1-1.5 parts of a lubricant and 0.1-0.3 part of a light stabilizer. The prepared composite material for enhancing the toughness of the polyformaldehyde material is good in toughness, good in wear resistance and suitable for preparing heavy-load mechanical parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyoxymethylene materials, and particularly relates to a composite material for enhancing the toughness of polyoxymethylene materials and a preparation method thereof. Background Art

[0002] Polyoxymethylene is widely used in aviation, machinery, precision instruments, automobiles, electronic appliances and other fields due to its similar specific strength and specific stiffness to metals, excellent creep resistance, wear resistance and electrical properties. It is one of the five major general engineering plastics. In addition, polyoxymethylene has also shown good growth momentum in emerging fields such as medical technology and sports equipment.

[0003] As a high-performance engineering plastic, polyoxymethylene has shown excellent performance in many fields, but it still faces some technical problems when used as heavy-duty mechanical parts: 1. Insufficient strength and stiffness: In heavy-duty mechanical parts, the material needs to withstand very high loads. Although the strength and stiffness of polyoxymethylene are good, they may be insufficient under extremely high loads. 2. Limited heat resistance: Heavy-duty mechanical parts often work in high-temperature environments, and polyoxymethylene has limited heat resistance, resulting in performance degradation. 3. Insufficient wear resistance: In heavy-duty mechanical parts, the material is often in a high-friction environment. Although the wear resistance of polyoxymethylene is good, it may be insufficient under extreme conditions. 4. Chemical resistance: In certain chemical environments, polyoxymethylene may be corroded, especially in acidic or alkaline environments. 5. Long-term performance stability: In long-term use, polyoxymethylene may age, resulting in performance degradation. Under long-term high load and high temperature conditions, polyoxymethylene may creep, affecting the shape and function of the parts.

[0004] In the prior art, ethylene-vinyl acetate is used as a compatibilizer to improve the toughness of polyoxymethylene, to improve the compatibility between polyoxymethylene and thermoplastic polyurethane elastomer, to enhance the adhesion of the blend between the two phases, and to improve the toughening efficiency. Thermoplastic polyurethane elastomer is a commonly used toughening modifier for polyoxymethylene, but the physical properties of polyoxymethylene application products are relatively high. In industry, in addition to improving the toughness of polyoxymethylene, the rigidity and strength of polyoxymethylene cannot be significantly reduced.

[0005] Therefore, there is an urgent need for a composite material having enhanced toughness of polyoxymethylene material and a preparation method thereof. Summary of the invention

[0006] The purpose of the present invention is to provide a composite material for enhancing the toughness of polyoxymethylene materials and a preparation method thereof.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] A composite material for enhancing the toughness of a polyoxymethylene material, comprising the following components by weight: 100 parts of polyoxymethylene, 10-20 parts of modified polyethylene, 5-15 parts of modified polytetrafluoroethylene, 5-10 parts of a toughening agent, 8-15 parts of a modified filler, 0.8-1.2 parts of an antioxidant, 1-1.5 parts of a lubricant, and 0.1-0.3 parts of a light stabilizer;

[0009] The preparation method of the modified polytetrafluoroethylene comprises the following steps by weight:

[0010] (1) mixing 1 part of polytetrafluoroethylene microspheres and 100 parts of 0.15-0.20 mol / L glucose aqueous solution, stirring evenly, and then subjecting the mixture to hydrothermal carbonization reaction at 165-170° C. for 12-15 h in a hydrothermal reactor, washing, and drying to obtain pretreated polytetrafluoroethylene;

[0011] (2) mixing 10 parts of 3-aminopropylmethyldiethoxysilane, 80-85 parts of ethanol, and 1 part of pretreated polytetrafluoroethylene, stirring and reacting at 40-45° C. for 4-6 hours, and drying to obtain polytetrafluoroethylene treated with a silane coupling agent;

[0012] (3) Mix 0.02 parts of carboxylated carbon nanotubes, 130-135 parts of thionyl chloride, and 200-220 parts of N,N-dimethylformamide, and stir at a speed of 250-270 r / min for 1-2 h to obtain chlorinated carboxylated carbon nanotubes;

[0013] (4) Mix 1 part of polytetrafluoroethylene treated with a silane coupling agent, 0.02 parts of chlorinated carboxylated carbon nanotubes, and 65-70 parts of N,N-dimethylformamide, react at 60-65° C. for 50-55 hours, and after the reaction, wash and spray dry to obtain modified polytetrafluoroethylene.

[0014] Polyoxymethylene, Dongguan Tianyi Plastic Co., Ltd., Model 570NC000.

[0015] 3-Aminopropylmethyldiethoxysilane, CAS: 3179-76-8.

[0016] Furthermore, the carboxylated carbon nanotubes have a diameter of 2-4 nm, a length of 0.5-2 μm, and a carboxyl content of 2.58 wt %, and are purchased from Xianfeng Nano, item number 100227.

[0017] Heavy-duty mechanical parts have high requirements for the wear resistance of polyoxymethylene. The present invention attempts to add polytetrafluoroethylene to improve the wear resistance of polyoxymethylene, but the effect is not ideal. The present invention improves the wear resistance of polyoxymethylene materials by modifying polytetrafluoroethylene. Carbon nanotubes are grafted into polytetrafluoroethylene. The carbon nanotubes grafted onto PTFE can enhance the strength and rigidity of PTFE. The addition of PTFE and carbon nanotubes can improve the surface properties of polyoxymethylene, thereby improving the wear resistance of the entire composite material. At the same time, the tensile strength of the polyoxymethylene material is improved.

[0018] Furthermore, the preparation method of the modified polyethylene comprises the following steps: adding polyethylene, urea-formaldehyde resin, ethanol, salicylic acid and 3-chloropropyltriethoxysilane in a weight ratio of 100: (15-20): (25-28): (4-9): (4-7) into an open mill, reacting at a temperature of 230-250° C. for 1-2 hours, and extruding and granulating at a temperature of 220-240° C. using an extruder to obtain modified polyethylene.

[0019] The present invention attempts to add polyethylene to the polyoxymethylene material to improve the notched impact strength, but the effect is not ideal. The present invention can improve the notched impact strength of the polyoxymethylene material by modifying polyethylene with urea-formaldehyde resin. This is because urea-formaldehyde resin can improve the interface compatibility between polyethylene and polyoxymethylene, increase the bonding strength between the two, and thus enhance the notched impact strength of the composite material.

[0020] 3-Chloropropyltriethoxysilane, CAS: 5089-70-3.

[0021] Urea-formaldehyde resin, Shengwanjia New Materials (Shandong) Co., Ltd., model SWJ-206415.

[0022] Furthermore, the preparation method of the modified filler comprises the following steps:

[0023] (1) mixing nano calcium carbonate, nano aluminum oxide and nano titanium oxide in a weight ratio of 1: (1.5-1.7): (0.3-0.5) to obtain a mixed filler;

[0024] (2) mixing 1 part by weight of a mixed filler, 0.2-0.4 parts of a silane coupling agent KH570, 20-25 parts of ethanol and 30-40 parts of deionized water, heating and stirring at 70-75° C. for 3-4 hours, cooling, filtering, washing and drying to obtain a pretreated mixed filler;

[0025] (3) Pretreated mixed filler, polytetrafluoroethylene emulsion, polyvinyl alcohol and 50-55wt% ethanol aqueous solution in a weight ratio of 1: (10-15): (0.1-0.4): (70-80) are mixed, dispersed evenly, and then spray-dried to obtain modified nanomaterials.

[0026] Furthermore, the particle size of nano calcium carbonate is 15-25nm and the specific surface area is 30-60m 2 / g; the particle size of nano-alumina is 10-30nm, and the specific surface area is 150-200m 2 / g; the particle size of nano titanium oxide is 5-15, and the specific surface area is 30-50m 2 / g. Purchased from Beijing Dekedao Gold Technology Co., Ltd.

[0027] The invention improves the compatibility of the filler and other components by adding the modified filler, thereby improving the tensile strength and elongation at break of the polyoxymethylene material.

[0028] Polytetrafluoroethylene emulsion, brand: DuPont, USA; model: TEFLON dispersion PTFE TE3970 tetrafluoro emulsion.

[0029] Polyvinyl alcohol, Shandong Hongquan Chemical Technology Co., Ltd., PVA2488.

[0030] Furthermore, the toughening agent is a toughening agent with a brand number of SH028A, which is purchased from Dongguan Shenghao Plastic Raw Materials Co., Ltd.

[0031] Furthermore, the weight ratio of the modified polyethylene, modified polytetrafluoroethylene and toughening agent is (13-16): (7-10): (6-8).

[0032] When the weight ratio of the modified polyethylene, modified polytetrafluoroethylene and toughening agent of the present invention is (13-16): (7-10): (6-8), the heat deformation temperature of the polyoxymethylene material can be improved.

[0033] Furthermore, the lubricant is polyethylene wax or calcium stearate.

[0034] Furthermore, the antioxidant is antioxidant 245 or antioxidant 1010.

[0035] Furthermore, the light stabilizer is 2-(2'-hydroxy-5'methyl)-benzotriazole. CAS: 2440-22-4.

[0036] The present invention also provides a method for preparing the composite material for enhancing the toughness of the polyoxymethylene material, comprising the following steps:

[0037] S1. Add the modified filler, antioxidant, light stabilizer, toughening agent and lubricant into a high-speed mixer, mix at 350-500 rpm for 5-10 min, then add the remaining components, mix at 400-450 rpm for 5-10 min to obtain a premixed mixture;

[0038] S2, adding the premixed mixture into a hopper of a twin-screw extruder, extruding and granulating through a twin-screw mixing reaction, to obtain a composite material with enhanced toughness of the polyoxymethylene material.

[0039] Furthermore, the temperature of the ten-stage twin-screw mixing extruder is set to 200-220° C., and the screw speed is 100-200 rpm.

[0040] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0041] 1. The present invention improves the impact resistance of the basic polyoxymethylene material by introducing specific toughening agents and modified fillers; the composite material not only maintains the original excellent mechanical strength, wear resistance and self-lubricating properties of polyoxymethylene, but also significantly enhances its toughness, so that the material can better absorb energy and is not prone to brittle fracture when subjected to external forces. In addition, the present invention also provides an efficient and environmentally friendly preparation process, including key steps such as selection and processing of raw materials, optimization of mixing ratios, and control of the molding process to ensure the high performance of the final product. The composite material obtained by the present invention is suitable for the manufacture of various parts that require both high strength and good toughness, such as structural parts in the automotive industry, housings of electronic and electrical products, and other components that require durable use.

[0042] 2. The present invention improves the wear resistance of the composite material that enhances the toughness of the polyoxymethylene material by modifying the polytetrafluoroethylene.

[0043] 3. The present invention can improve the notched impact strength of the composite material that enhances the toughness of the polyoxymethylene material by modifying polyethylene with urea-formaldehyde resin.

[0044] 4. The present invention improves the compatibility of the filler and other components by adding modified fillers, thereby improving the tensile strength and elongation at break of the composite material that enhances the toughness of the polyoxymethylene material. DETAILED DESCRIPTION

[0045] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] Example 1

[0047] The present embodiment provides a composite material for enhancing the toughness of polyoxymethylene materials, including the following components by weight: 100 parts of polyoxymethylene, 15 parts of modified polyethylene, 8 parts of modified polytetrafluoroethylene, 7 parts of toughening agent, 12 parts of modified filler, 1 part of antioxidant, 1.2 parts of lubricant, and 0.2 parts of light stabilizer.

[0048] The lubricant is calcium stearate, the antioxidant is antioxidant 245, and the light stabilizer is 2-(2'-hydroxy-5'methyl)-benzotriazole.

[0049] The preparation method of the modified polytetrafluoroethylene comprises the following steps by weight:

[0050] (1) 1 part of polytetrafluoroethylene microspheres and 100 parts of a glucose aqueous solution with a concentration of 0.17 mol / L were mixed, stirred evenly, subjected to hydrothermal carbonization reaction at 168° C. in a hydrothermal reactor for 14 h, washed, and dried to obtain pretreated polytetrafluoroethylene;

[0051] (2) 10 parts of 3-aminopropylmethyldiethoxysilane, 82 parts of ethanol, and 1 part of pretreated polytetrafluoroethylene were mixed, stirred at 42° C. for 5 hours, and dried to obtain polytetrafluoroethylene treated with a silane coupling agent;

[0052] (3) 0.02 parts of carboxylated carbon nanotubes, 132 parts of thionyl chloride, and 210 parts of N,N-dimethylformamide were mixed at a speed of 260 r / min and stirred for 1.6 h to obtain chlorinated carboxylated carbon nanotubes;

[0053] (4) 1 part of polytetrafluoroethylene treated with a silane coupling agent, 0.02 parts of acyl chloride carboxylated carbon nanotubes and 67 parts of N,N-dimethylformamide were mixed and reacted at 62° C. for 52 hours. After the reaction was completed, the mixture was washed and spray-dried to obtain modified polytetrafluoroethylene.

[0054] Polyoxymethylene, Dongguan Tianyi Plastic Co., Ltd., Model 570NC000.

[0055] 3-Aminopropylmethyldiethoxysilane, CAS: 3179-76-8.

[0056] The carboxylated carbon nanotubes have a diameter of 2-4 nm, a length of 0.5-2 μm, and a carboxyl content of 2.58 wt %, and were purchased from Xianfeng Nano, item number 100227.

[0057] The preparation method of the modified polyethylene comprises the following steps: adding polyethylene, urea-formaldehyde resin, ethanol, salicylic acid and 3-chloropropyltriethoxysilane in a weight ratio of 100:18:26:7:5 into an open mill, reacting at a temperature of 240° C. for 1.6 hours, and extruding and granulating at a temperature of 230° C. using an extruder to obtain the modified polyethylene.

[0058] 3-Chloropropyltriethoxysilane, CAS: 5089-70-3.

[0059] Urea-formaldehyde resin, Shengwanjia New Materials (Shandong) Co., Ltd., model SWJ-206415.

[0060] Polyethylene, LG Chemical, South Korea, model BE0400.

[0061] The preparation method of the modified filler comprises the following steps:

[0062] (1) mixing nano calcium carbonate, nano aluminum oxide and nano titanium oxide in a weight ratio of 1:1.6:0.4 to obtain a mixed filler;

[0063] (2) mixing 1 part by weight of a mixed filler, 0.3 part by weight of a silane coupling agent KH570, 22 parts by weight of ethanol, and 35 parts by weight of deionized water, heating and stirring at 72° C. for 3.5 hours, cooling, filtering, washing, and drying to obtain a pretreated mixed filler;

[0064] (3) Pretreated mixed filler, polytetrafluoroethylene emulsion, polyvinyl alcohol and 52 wt % ethanol aqueous solution in a weight ratio of 1:12:0.3:75 are mixed, dispersed evenly, and then spray-dried to obtain modified nanomaterials.

[0065] The particle size of nano calcium carbonate is 15-25nm and the specific surface area is 30-60m 2 / g; the particle size of nano-alumina is 10-30nm, and the specific surface area is 150-200m 2 / g; the particle size of nano titanium oxide is 5-15, and the specific surface area is 30-50m 2 / g. Purchased from Beijing Dekedao Gold Technology Co., Ltd.

[0066] Polytetrafluoroethylene emulsion, brand: DuPont, USA; model: TEFLON dispersion PTFE TE3970 tetrafluoro emulsion.

[0067] Polyvinyl alcohol, Shandong Hongquan Chemical Technology Co., Ltd., PVA2488.

[0068] The toughening agent is a toughening agent with the brand name SH028A, which is purchased from Dongguan Shenghao Plastic Raw Materials Co., Ltd.

[0069] The method for preparing the composite material for enhancing the toughness of polyoxymethylene material comprises the following steps:

[0070] S1, adding the modified filler, antioxidant, light stabilizer, toughening agent and lubricant into a high-speed mixer, mixing at 400 rpm for 7 min, then adding the remaining components, mixing at 420 rpm for 8 min, to obtain a premixed mixture;

[0071] S2. Add the premixed mixture into a hopper of a twin-screw extruder, and granulate it through twin-screw mixing reaction extrusion. The temperature of the ten-stage twin-screw mixing extruder is set to 210° C., and the screw speed is 150 rpm, to obtain a composite material with enhanced toughness of the polyoxymethylene material.

[0072] Example 2

[0073] This embodiment provides a composite material for enhancing the toughness of a polyoxymethylene material, comprising the following components by weight: 100 parts of polyoxymethylene, 10 parts of modified polyethylene, 15 parts of modified polytetrafluoroethylene, 5 parts of a toughening agent, 15 parts of a modified filler, 0.8 parts of an antioxidant, 1.5 parts of a lubricant, and 0.1 parts of a light stabilizer;

[0074] The lubricant is calcium stearate. The antioxidant is antioxidant 1010. The light stabilizer is 2-(2'-hydroxy-5'methyl)-benzotriazole. CAS: 2440-22-4.

[0075] The preparation method of the modified polytetrafluoroethylene comprises the following steps by weight:

[0076] (1) mixing 1 part of polytetrafluoroethylene microspheres and 100 parts of 0.20 mol / L glucose aqueous solution, stirring evenly, subjecting the mixture to hydrothermal carbonization reaction at 170° C. for 12 h in a hydrothermal reactor, washing, and drying to obtain pretreated polytetrafluoroethylene;

[0077] (2) 10 parts of 3-aminopropylmethyldiethoxysilane, 85 parts of ethanol, and 1 part of pretreated polytetrafluoroethylene were mixed, stirred at 40° C. for 6 hours, and dried to obtain polytetrafluoroethylene treated with a silane coupling agent;

[0078] (3) 0.02 parts of carboxylated carbon nanotubes, 130 parts of thionyl chloride, and 220 parts of N,N-dimethylformamide were mixed at a speed of 250 r / min and stirred for 2 h to obtain chlorinated carboxylated carbon nanotubes;

[0079] (4) 1 part of polytetrafluoroethylene treated with a silane coupling agent, 0.02 parts of acyl chloride carboxylated carbon nanotubes and 65 parts of N,N-dimethylformamide were mixed and reacted at 65° C. for 50 h. After the reaction was completed, the mixture was washed and spray-dried to obtain modified polytetrafluoroethylene.

[0080] Polyoxymethylene, Dongguan Tianyi Plastic Co., Ltd., Model 570NC000.

[0081] 3-Aminopropylmethyldiethoxysilane, CAS: 3179-76-8.

[0082] The carboxylated carbon nanotubes have a diameter of 2-4 nm, a length of 0.5-2 μm, and a carboxyl content of 2.58 wt %, and were purchased from Xianfeng Nano, item number 100227.

[0083] Polytetrafluoroethylene microspheres, Beijing Zhongke Keyou Nanotechnology Co., Ltd., bare spheres, solid, particle size 1-5μm.

[0084] The preparation method of the modified polyethylene comprises the following steps: adding polyethylene, urea-formaldehyde resin, ethanol, salicylic acid and 3-chloropropyltriethoxysilane in a weight ratio of 100:15:25:9:4 into an open mill, reacting at a temperature of 250°C for 1 hour, and extruding and granulating at a temperature of 240°C using an extruder to obtain the modified polyethylene.

[0085] 3-Chloropropyltriethoxysilane, CAS: 5089-70-3.

[0086] Polyethylene, LG Chemical, South Korea, model BE0400.

[0087] Urea-formaldehyde resin, Shengwanjia New Materials (Shandong) Co., Ltd., model SWJ-206415.

[0088] The preparation method of the modified filler comprises the following steps:

[0089] (1) mixing nano calcium carbonate, nano aluminum oxide and nano titanium oxide in a weight ratio of 1:1.5:0.5 to obtain a mixed filler;

[0090] (2) mixing 1 part by weight of a mixed filler, 0.2 parts by weight of a silane coupling agent KH570, 25 parts by weight of ethanol, and 40 parts by weight of deionized water, heating and stirring at 70° C. for 4 h, cooling, filtering, washing, and drying to obtain a pretreated mixed filler;

[0091] (3) Pretreated mixed filler, polytetrafluoroethylene emulsion, polyvinyl alcohol and 55 wt % ethanol aqueous solution in a weight ratio of 1:10:0.4:70 are mixed, dispersed evenly, and then spray-dried to obtain modified nanomaterials.

[0092] The particle size of nano calcium carbonate is 15-25nm and the specific surface area is 30-60m 2 / g; the particle size of nano-alumina is 10-30nm, and the specific surface area is 150-200m 2 / g; the particle size of nano titanium oxide is 5-15, and the specific surface area is 30-50m 2 / g. Purchased from Beijing Dekedao Gold Technology Co., Ltd.

[0093] Polytetrafluoroethylene emulsion, brand: DuPont, USA; model: TEFLON dispersion PTFE TE3970 tetrafluoro emulsion.

[0094] Polyvinyl alcohol, Shandong Hongquan Chemical Technology Co., Ltd., PVA2488.

[0095] The toughening agent is a toughening agent with the brand name SH028A, which is purchased from Dongguan Shenghao Plastic Raw Materials Co., Ltd.

[0096] The method for preparing the composite material for enhancing the toughness of polyoxymethylene material comprises the following steps:

[0097] S1, adding the modified filler, antioxidant, light stabilizer, toughening agent and lubricant into a high-speed mixer, mixing at 350 rpm for 10 min, then adding the remaining components, mixing at 400 rpm for 10 min, to obtain a premixed mixture;

[0098] S2. Add the premixed mixture into a hopper of a twin-screw extruder, and granulate it through twin-screw mixing reaction extrusion. The temperature of the ten-stage twin-screw mixing extruder is set to 200° C., and the screw speed is 200 rpm to obtain a composite material with enhanced toughness of the polyoxymethylene material.

[0099] Comparative Example 1

[0100] The difference between this comparative example and Example 1 is: a composite material for enhancing the toughness of polyoxymethylene material, comprising the following components by weight: 100 parts of polyoxymethylene, 5 parts of modified polyethylene, 20 parts of modified polytetrafluoroethylene, 12 parts of toughening agent, 5 parts of modified filler, 1 part of antioxidant, 1.2 parts of lubricant, and 0.2 parts of light stabilizer.

[0101] Comparative Example 2

[0102] The difference between this comparative example and Example 1 is that the modified polytetrafluoroethylene is replaced by polytetrafluoroethylene microspheres. Polytetrafluoroethylene microspheres, Beijing Zhongke Keyou Nanotechnology Co., Ltd., bare spheres, solid, particle size 1-5 μm.

[0103] Comparative Example 3

[0104] The difference between this comparative example and Example 1 is that the modified polyethylene is replaced by polyethylene. Polyethylene, LG Chemical of South Korea, model BE0400.

[0105] Comparative Example 4

[0106] The difference between this comparative example and Example 1 is that nano calcium carbonate, nano aluminum oxide and nano titanium oxide are mixed in a weight ratio of 1:1:1 to obtain a mixed filler.

[0107] Comparative Example 5

[0108] The difference between this comparative example and Example 1 is that the preparation method of the modified filler comprises the following steps:

[0109] (1) mixing nano calcium carbonate, nano aluminum oxide and nano titanium oxide in a weight ratio of 1:1.6:0.4 to obtain a mixed filler;

[0110] (2) Mix 1 part by weight of a mixed filler, 0.3 part by weight of a silane coupling agent KH570, 22 parts by weight of ethanol and 35 parts by weight of deionized water, heat and stir at 72° C. for 3.5 hours, cool, filter, wash and dry to obtain a modified filler.

[0111] Comparative Example 6

[0112] The difference between this comparative example and Example 1 is that the particle size of nano calcium carbonate is 40-50nm, and the specific surface area is 10-20m 2 / g; the particle size of nano-alumina is 60-80nm, and the specific surface area is 20-50m 2 / g; the particle size of nano titanium oxide is 50-60, and the specific surface area is 20-30m 2 / g. Beijing Dekedaojin Technology Co., Ltd.

[0113] Performance Testing

[0114] The composite materials for enhancing the toughness of polyoxymethylene materials prepared in Examples 1-2 and Comparative Examples 1-6 were subjected to performance tests. The results are shown in Table 1.

[0115] Table 1 Performance test results

[0116]

[0117]

[0118] From the above performance test results, it can be seen that the composite materials for enhancing the toughness of polyoxymethylene materials of Examples 1-2 have excellent performance, especially the comprehensive performance of Example 1 is the most outstanding, which is mainly due to the synergistic effect between the components. However, since the weight ratio of modified polyethylene, modified polytetrafluoroethylene and toughening agent in Example 2 is not in the range of (13-16): (7-10): (6-8), the heat deformation temperature is lower than 190°C.

[0119] However, since the comparative examples do not adopt the necessary technical solutions, they are significantly worse than the embodiments in the corresponding performance tests. In comparative example 1, the ratio of the components is changed, and it can be seen that the comprehensive performance effect is reduced. In comparative example 2, the modified polytetrafluoroethylene is replaced by polytetrafluoroethylene microspheres, and the wear resistance of the polyoxymethylene material is reduced; in comparative example 3, the modified polyethylene is replaced by polyethylene, and the notched impact strength of the polyoxymethylene material is reduced; in comparative example 4, the filler ratio is different, in comparative example 5, the filler modification method is different, and in comparative example 6, the filler parameters are different. It can be seen from the results that the tensile strength and elongation at break of the polyoxymethylene material are reduced. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.

[0120] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A composite material for enhancing the toughness of a polyoxymethylene material, characterized in that: The invention comprises the following components by weight: 100 parts of polyoxymethylene, 10-20 parts of modified polyethylene, 5-15 parts of modified polytetrafluoroethylene, 5-10 parts of toughening agent, 8-15 parts of modified filler, 0.8-1.2 parts of antioxidant, 1-1.5 parts of lubricant and 0.1-0.3 parts of light stabilizer; The preparation method of the modified polytetrafluoroethylene comprises the following steps by weight: (1) mixing 1 part of polytetrafluoroethylene microspheres and 100 parts of a 0.15-0.20 mol / L glucose aqueous solution, stirring evenly, and then subjecting the mixture to a hydrothermal carbonization reaction at 165-170° C. for 12-15 h in a hydrothermal reactor, washing, and drying to obtain pretreated polytetrafluoroethylene; (2) mixing 10 parts of 3-aminopropylmethyldiethoxysilane, 80-85 parts of ethanol, and 1 part of pretreated polytetrafluoroethylene, stirring and reacting at 40-45° C. for 4-6 hours, and drying to obtain polytetrafluoroethylene treated with a silane coupling agent; (3) Mix 0.02 parts of carboxylated carbon nanotubes, 130-135 parts of thionyl chloride, and 200-220 parts of N,N-dimethylformamide, and stir at a speed of 250-270 r / min for 1-2 h to obtain chlorinated carboxylated carbon nanotubes; (4) Mix 1 part of polytetrafluoroethylene treated with a silane coupling agent, 0.02 parts of chlorinated carboxylated carbon nanotubes, and 65-70 parts of N,N-dimethylformamide, react at 60-65° C. for 50-55 hours, and after the reaction, wash and spray dry to obtain modified polytetrafluoroethylene.

2. The composite material for enhancing the toughness of polyoxymethylene material according to claim 1, characterized in that: The preparation method of the modified polyethylene comprises the following steps: adding polyethylene, urea-formaldehyde resin, ethanol, salicylic acid and 3-chloropropyltriethoxysilane in a weight ratio of 100:(15-20):(25-28):(4-9):(4-7) into an open mill, reacting at a temperature of 230-250° C. for 1-2 hours, and extruding and granulating at a temperature of 220-240° C. using an extruder to obtain the modified polyethylene.

3. The composite material for enhancing the toughness of polyoxymethylene material according to claim 2, characterized in that: The preparation method of the modified filler comprises the following steps: (1) mixing nano calcium carbonate, nano aluminum oxide and nano titanium oxide in a weight ratio of 1: (1.5-1.7): (0.3-0.5) to obtain a mixed filler; (2) mixing 1 part by weight of a mixed filler, 0.2-0.4 parts of a silane coupling agent KH570, 20-25 parts of ethanol and 30-40 parts of deionized water, heating and stirring at 70-75° C. for 3-4 hours, cooling, filtering, washing and drying to obtain a pretreated mixed filler; (3) Pretreated mixed filler, polytetrafluoroethylene emulsion, polyvinyl alcohol and 50-55wt% ethanol aqueous solution in a weight ratio of 1: (10-15): (0.1-0.4): (70-80) are mixed, dispersed evenly, and then spray-dried to obtain modified nanomaterials.

4. The composite material for enhancing the toughness of polyoxymethylene material according to claim 3, characterized in that: The particle size of nano calcium carbonate is 15-25nm and the specific surface area is 30-60m 2 / g; the particle size of nano-alumina is 10-30nm, and the specific surface area is 150-200m 2 / g; the particle size of nano titanium oxide is 5-15, and the specific surface area is 30-50m 2 / g. Purchased from Beijing Dekedao Gold Technology Co., Ltd.

5. The composite material for enhancing the toughness of polyoxymethylene material according to claim 4, characterized in that: The toughening agent is a toughening agent of brand SH028A.

6. The composite material for enhancing the toughness of polyoxymethylene material according to claim 5, characterized in that: The weight ratio of the modified polyethylene, modified polytetrafluoroethylene and toughening agent is (13-16): (7-10): (6-8).

7. The composite material for enhancing the toughness of polyoxymethylene material according to claim 1, characterized in that: The lubricant is polyethylene wax or calcium stearate.

8. The composite material for enhancing the toughness of polyoxymethylene material according to claim 1, characterized in that: The antioxidant is antioxidant 245 or antioxidant 1010.

9. A method for preparing a composite material for enhancing the toughness of polyoxymethylene materials according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Add the modified filler, antioxidant, light stabilizer, toughening agent and lubricant into a high-speed mixer, mix at 350-500 rpm for 5-10 min, then add the remaining components, mix at 400-450 rpm for 5-10 min to obtain a premixed mixture; S2, adding the premixed mixture into a hopper of a twin-screw extruder, extruding and granulating through a twin-screw mixing reaction, to obtain a composite material with enhanced toughness of the polyoxymethylene material.

10. The method for preparing a composite material for enhancing the toughness of polyoxymethylene materials according to claim 9, characterized in that: The temperature of the ten-stage twin-screw mixing extruder is set at 200-220° C., and the screw speed is 100-200 rpm.